A Atuação da Universidade Federal de Uberlândia à Luz dos Princípios de uma Universidade Empreendedora dentro de um Contexto Regional - Nunes, Rebecca Thaffenne Santos Oliveira (2025)
Background: Since the 1980s, Brazilian universities have begun to adopt a more active role in fostering entrepreneurship, integrating teaching, research and partnerships with the productive sector. This movement has resulted in the Entrepreneurial University model, which seeks to generate innovation, boost the creation of startups and promote social impact. However, entrepreneurial actions in universities are not homogeneous, and their approaches vary according to the institutional and regional contexts. In the case of the Federal University of Uberlândia (UFU), despite its strategic role in the Triângulo Mineiro, the institution still faces challenges in integrating its initiatives into its regional ecosystem, which limits its impact compared to other Brazilian universities. Objective: The aim of this study is to propose an Entrepreneurial University model based on an analysis of UFU's entrepreneurial actions. Method: The methodology adopted in this research was qualitative and descriptive, with secondary data collection carried out using internal UFU documents, such as regulations and manual. Primary data was also collected through 18 interviews. Data analysis was conducted by means of Content Analysis, using Atlas.ti software to operationalize the analysis. Results: The analysis resulted in the identification of 28 categories organized into three main axes: entrepreneurial actions, incorporation of the principles of an Entrepreneurial University and obstacles/difficulties faced. The most relevant entrepreneurial actions included the central role of the UFU Business Incubation Center, which stands out in the development of startups and the creation of innovative solutions, as well as initiatives aimed at technology transfer and the promotion of innovation events. However, the main challenges identified were the implementation of actions in isolation, the scarcity of financial resources, limiting the expansion of initiatives and infrastructure, and excessive bureaucracy, which slows down the implementation of projects and discourages innovation. These obstacles highlight the need for greater institutional integration, simplification of processes and external fundraising as essential pillars for improving UFU's entrepreneurial principles. In the end, implementing the model requires overcoming these challenges, promoting coordination between its academic and administrative units, increasing financial resources and reducing bureaucracy in processes, guaranteeing a more favorable environment for innovation and entrepreneurship. Adherence to the area of concentration (Regionality and Management) and the line of research: This study is part of the PPGAdm area of concentration, in line with the line of research focused on analyzing the role of the university as a central organization in its regional context. The research investigates how the university contributes to fostering innovation and entrepreneurship, focusing on the impact of its actions on the region. It examines the university's interaction with the local ecosystem and the promotion of partnerships that drive regional development. By exploring these dynamics, the research seeks to understand how the university's entrepreneurial actions align with the economic, social and cultural characteristics of the region, considering the importance of regional management in consolidating these actions. Impact and innovative character in intellectual production: The innovative character of the research lies in the interdisciplinary approach and the application of the concepts of the Entrepreneurial University in a specific regional context, with the aim of offering original solutions and information for the development of entrepreneurship and innovation. We expect the results can guide public policies, regional development programs and institutional strategies of federal universities, contributing to the strengthening of the ecosystem in the university's region and potentially in other regions of Brazil facing similar challenges. Economic, social and regional impact: This study is important for supporting entrepreneurial actions and strengthening regional development in the Triângulo Mineiro, highlighting UFU's contribution to the progress of Uberlândia and its recognition as an innovative environment. The research aims to improve understanding of entrepreneurial actions and encourage initiatives that benefit society, promoting regional development and integrating local players. It also seeks to stimulate local economic growth through joint projects and courses aligned with market demands, strengthening the regional economy. UFU, with its campuses in several cities, has great influence in the region, contributing to regional development and improving quality of life. Regional implications: The research contributes to strengthening the Triângulo Mineiro region by identifying and analyzing UFU's entrepreneurial actions, promoting local economic and social development. The university's actions, with its programs and partnerships, play a significant role in fostering entrepreneurship, generating new opportunities and driving growth in the region. By aligning itself with the needs and demands of the local market, UFU can become a focal point for sustainable regional development, promoting improvements in the quality of life and the integration of the various social and economic players. Sustainable Development Goals addressed in the research: The research is aligned with several Sustainable Development Goals (SDGs). In relation to SDG 4: Quality Education, it investigates how the integration of entrepreneurial actions in teaching contributes to the training of innovative students. SDG 8: Decent Work and Economic Growth highlights the role of UFU in promoting entrepreneurship, with a view to creating jobs and regional economic growth. With regard to SDG 9: Industry, Innovation and Infrastructure, the study examines how UFU's entrepreneurial actions have contributed to the creation of jobs and regional economic growth. Finally, SDG 17: Partnerships and Means of Implementation is addressed by analyzing the importance of partnerships between universities, the private sector and government for regional development and innovation.